Role of Early Rehabilitation Intervention in Restoring Functional State of Cardiovascular System of Women with Postmastectomy Syndrome - Ю. А. Бріскін; Т. Є. Одинець (OVS LLC, 2016)
The purpose of the research is to determine the feasibility of early rehabilitation intervention in restoring the functional state of the cardiovascular system of women with postmastectomy syndrome. Materials and methods: analysis and collation of the literature sources and empirical data; computer rheography; methods of mathematical statistics. The research involved 135 women with postmastectomy syndrome suffering from Madden's radical mastectomy. Results. The research showed that early rehabilitation intervention is effective exlusively in terms of improving the capacity of the left ventricle in women with postmastectomy syndrome by the annual monitoring indicators.